Novel feeding system to promote establishment of breastfeeds after preterm birth: a randomized controlled trial - Simmer, K (J Perinatol, 2016)
OBJECTIVE: We aimed to determine if a novel feeding system where milk only flowed when the preterm infant created a vacuum would influence time to full oral feeds, the length of stay (LOS) in hospital and breastfeeding at discharge. STUDY DESIGN: This was a randomized controlled trial in the tertiary neonatal intensive care unit at King Edward Memorial Hospital, Perth, Australia. Eligibility criteria were: preterm infants of gestational age 25 to 34 weeks receiving >75% human milk by gastric tube. Infants were randomly assigned to being fed with a novel teat (NT) or conventional teat (CT). Intention to treat analysis was performed. RESULT: Time to full suck feeds was not different between groups. LOS was shorter (mean: 2.5 days; P=0.026) and less formula was fed at discharge in the NT group (P=0.036). CONCLUSION: Use of a NT that releases milk when the infant applies vacuum while establishing breastfeeding reduces duration of hospitalization of preterm infants.